AlphaTracker: a multi-animal tracking and behavioral analysis tool - Chen, Zexin; Zhang, Ruihan; Fang, Hao-Shu; Zhang, Yu E.; Bal, Aneesh; Zhou, Haowen; Rock, Rachel R.; Padilla-Coreano, Nancy; Keyes, Laurel R.; Zhu, Haoyi; Li, Yong-Lu; Komiyama, Takaki; et al. (Frontiers in Behavioral Neuroscience, 2023)
Computer vision tools have emerged as a powerful tool to elevate behavioral research. This protocol describes a computer vision machine learning pipeline called AlphaTracker, which has minimal hardware requirements and produces reliable tracking of multiple unmarked animals, as well as behavioral clustering. AlphaTracker combines a top-down pose-estimation software combined with unsupervised clustering to facilitate behavioral motif discovery that will accelerate behavioral research. All steps of the protocol are provided as open-source software with graphic user interfaces or implementable with command-line prompts. Users with a graphical processing unit (GPU) can model and analyze animal behaviors of interest in less than a day. AlphaTracker greatly facilitates the analysis of the mechanism of individual/social behavior and group dynamics.